ÅNDEBØRN - Samuelsen, Helle (Tidsskriftet Antropologi, 1998)
Helle Samuelsen: Spirit Children According to local cosmology among the Bissa of Burkina Faso, small children up to 3-4 years of age are seen as balancing between the living and the spiritual worlds. At this early stage in their lives, they are in a transitional state with a certain attachment to the world of spirits and ancestors. On the one hånd, children are considered vulnerable and thus eligible for parental protection, while on the other hånd, they are perceived as powerful in that they represent the spiritual world. This local cosmology of early childhood liminality is inscribed in children’s bodies through daily practices of preventing and treating illness. Practices for controlling bodily orifices, viewed as thresholds between inner body and the extemal world, and controlling spatial boundaries between village and bush, are important in regulating the relationship between the living and the spiritual worlds. Analytically, the body can bc seen as part of the topology where local cosmology is unfolded. The article shows how studies of daily health care practices aimed at controlling the liminality of small children contribute to understanding how local cosmology is practiced in everyday life. It is argued that although children are not studied as individual agents in this article, a focus on children gives insight into other and more general aspects of the local culture.